Design and development of a pineapple roll tart making machine - Pua, Ming Yee (2011)
Majority of pineapple rolled tarts are produced manually. Production is therefore slow and supply is unable to meet the market demand. A rolled tart making machine is essential for the efficient mass production of pineapple rolled tart. A machine that would reduce processing time, labour, and operating cost and at the same time, affordable for small-scale industries, was designed. Food properties are varying with time. Before design processes were carried out, effect of dough and jam formulations on its properties and kinetic studies of jam were studied. Effects of pineapple bakery jams with different sugar compositions (0% to 33.3%) were evaluated at ambient temperature based on total soluble solid (TSS), pH, viscosity, and moisture content. Simultaneously, effects of different butter (23% to 45%), sugar (0% to 20%) and corn flour (0% to 15%) compositions on hardness and stickiness of pineapple tart short dough were determined. There were significantly increased (p< 0.05) in total soluble solids (TSS), viscosity, and moisture content of jams at different sugar percentages, but no significant changes in pH were observed. In textural analytical test, significant changes (p< 0.05) in hardness and stickiness of pineapple tart short dough with different compositions of butter, sugar, and corn flour were found. Cooking rate of pineapple bakery jam was investigated and the effects of cooking temperature (70°C to 100°C), stirring speed (20 rpm to 100 rpm) and batch volume (2 to 6 liters) on rate constant were examined. The linear relationship between the logarithmic total soluble solids gain ratios of cooked jam and the cooking time showed that the cooking rate followed the equation of first-order chemical reaction. The cooking rates increased with cooking temperature and stirring speed, but decreased with increasing batch volume. The activation energy of cooking process was 42.49 kJ/mol. Present investigation of cooking rate constant will be useful in designing more efficient jam cookers with higher ratio of effective heating surface to batch volume of fruit pulp. Engineering design processes were carried out to develop the conceptual designs, which were generated with Computer Aided Design (CAD) software and evaluated based on customers’ requirements. The basic decision matrix was used as a decision making tool for selecting the best design. The fabricated machine was tested at different screw rotating speeds and dough formulations. The rolled tart throughput rates increased significantly (p<0.05) with screw rotating speeds and butter percentages of dough. However, it decreased significantly (p<0.01) with sugar and corn flour percentages. The hardness of baked tart and the hardness and stickiness of unbaked tarts showed no significant difference between various screw rotating speeds and the manual method. It was found that the rolled tart produced by this machine was acceptable in texture and mouth feel. The maximum and minimum rates for the standard dough formula were 4320 pieces per hour and 720 pieces per hour, respectively. The operating costs of making tarts using the machine with the highest rate were reduced by 92.05%, compared to the manual method. This machine achieved the objectives of research which can produce tarts at high rate, low operating and labour costs and it is affordable for small scale industries. This research provided the guideline how to manipulate the dough and jam formulation, and simple way to determine the end point of jam cooking.